Using the fossil charcoal and pollen records from Elands Bay Cave and Boomplaas Cave, South Africa, to reconstruct variability in local hydroclimate and seasonality - Khumalo, Wendy (Department of Geological Sciences, 2023)
Global climate change is well documented and recorded by various marine and terrestrial archives, predominantly by benthic ocean sediment and ice cores. These records are characterized by cyclical variation, suggesting changing polar ice volumes from glacial to interglacial conditions, driven by Milankovich cycles and greenhouse gas concentration feedbacks. While these records have informed much of our understanding of past climate variability, they are from either the deep ocean or high latitudes, with a huge bias to the Northern Hemisphere. More terrestrial, mid latitude, Southern Hemisphere (SH) palaeoclimate records are needed to plug this gap in our knowledge. With a rapidly changing and uncertain climate future, these new records should intersect with past records of human activity. South Africa (SA) has a huge geographic advantage, sitting at the confluence of the Southern Atlantic and Indian Ocean systems and hosting an almost unprecedented rich record of human occupancy spanning the last 2.6 Ma, but particularly the Last Glacial Maximum (LGM). An equator-wards shift in the SH Westerlies has long been used to account for increased precipitation in SA during the LGM. While this narrative is challenged by a few records from the Southern Cape, which suggest aridity during the LGM, it remains an overarching idea. In this thesis, I test these two apparently contradictory climate responses by using fossil charcoal and pollen records from two archaeological sites: Boomplaas Cave (BPC) in the Year-round Rainfall Zone (YRZ), and Elands Bay Cave (EBC) in the Winter Rainfall Zone (WRZ). By quantifying changes in Mean Annual Temperature (MAT), Total Annual Precipitation (TAP), and Dry Quarter Precipitation (DQP), I explore the potential of using archaeological charcoal to reconstruct a palaeoclimate throughout the LGM in SA. Specifically, I use a Canonical Correspondence Analysis to interrogate the species response to modern climate and a Weighted Average – Partial Least Squared regression to reconstruct paleoclimate. These results display the promising ability of fossil charcoal records to represent changes in hydroclimate given a few conditions. Both sites record an average decrease in MAT of 5°C at the LGM compared to modern conditions, consistent with existing regional records. Precipitation results from BPC show ~200mm less precipitation around the LGM compared to present day, this is consistent with other proxies from the Southern Cape, as well as global climate model results suggesting decreased precipitation in the region. The EBC charcoal record proved its ability to reconstruct MAT trends and (given a few conditions) the potential to reproduce TAP results. Interestingly, at the LGM, the EBC pollen record suggests a decrease in TAP of ~150mm, which does not agree with existing records (see chapter 2). This decrease in LGM TAP recorded at both sites, together with reconstructions of DQP are used to argue that the WRZ did not expand to reach BPC during the LGM. Overall, the new records present here are more consistent with a pole-wards shift in the SH Westerlies, challenging the long-held notion of a wet LGM in SA.